Prevalence and associated risk factors of soll-transmitted helminth infection among children in Brgy. Francisco de Castro, Gen. Mariano Alvarez, Cavite, Philippines - Bernardion, Justine S. Bilas, Abegail A. Evangelista, Nicole B. Fetizanan, Abijah Glad M. 4 0 16; 5
ABSTRACT: Soil-transmitted helminthiasis is a parasitic worm infection that is acquired from feces-contaminated soil in places with poor sanitation. Ascaris lumbricoides, Trichuris trichiuria, Nectator americanus, and Ancylostoma duodenale are the most common worm infecting humans, affecting low- and middle- income nations including the Philippines. The prevalence of STH in the country is still concerning even after years of implementation of various programs including Integrated Helminth Control Program. Thus, it is imperative to reasses the prevalence of infection and the risk factors associated with it. In this study, 233 randomly selected pre-school and school children from Brgy. Francisco de Castro in General Mariano Alvarez, Cavite were examined for the infection using Formalin Ethyl Acetate Concentration Technique in detecting parasites. Validated survey questionnaires were also answered by their parents to assess the risk factors and log-binomial regresion model was the statistical test used to determine the association of the prevalence of STH to the risk factors. Out of the 233 children, 8.6% tested positive with A. lumbricoides, 1.3% for T. trichiuria, and 0.4% for S. stercoralis with overall prevalence of 9.4%. There was no hookworm detected but Strongyloides stercoralis was detected in one patient. In addition, out of the risk factors that were tested, only the history of deworming had significant association with the prevalence of STH infection. Overall, the researchers were unable to generalize the association between the prevalence of STH infection in children with the risk factors (sociodemographic, environmental, behavior of parents and children, and close contact with domestic animals) tested due lack of evidence in the sample population utilized in the study. Keywords STH, NTD, Strongyloides, Soil-transmitted Helminths, ascariasis, trichuriasis
Undergraduate Thesis: (BS in Biology major in Medical Biology) - Pamantasan ng Lungsod ng Maynila, 2023
Keywords: 2 -- 0; 6; 20; 20; 2